2013
DOI: 10.1007/s00590-013-1288-9
|View full text |Cite
|
Sign up to set email alerts
|

Medial humeral condyle fractures in adolescents: treatment and complications

Abstract: The very rare isolated medial humeral condyle fractures in children and adolescents pose significant problems to orthopedic surgeons such as ulnar nerve injury, trochlear irregularities, fishtail deformity and motion loss. Six adolescent boys with displaced medial humeral condyle fractures with an average age of 14.8 (range 12-17) were included in this study. Patients were followed-up with a mean of 39.8 months (range 21-72). In three patients, there were clinical signs of ulnar nerve dysfunction at initial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 14 publications
0
17
0
5
Order By: Relevance
“…Range of motion was used as the outcome measure in seven studies [ 12 , 14 , 16 , 19 , 21 , 24 , 25 ]. Loss of extension was seen in 12 patients (67 %) [ 12 , 14 , 16 , 21 , 25 ] and a valgus deformity was seen in seven patients (39 %) [ 12 , 14 , 16 , 18 , 24 ]. Clinical symptoms were described in 11 patients [ 13 , 16 , 21 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Range of motion was used as the outcome measure in seven studies [ 12 , 14 , 16 , 19 , 21 , 24 , 25 ]. Loss of extension was seen in 12 patients (67 %) [ 12 , 14 , 16 , 21 , 25 ] and a valgus deformity was seen in seven patients (39 %) [ 12 , 14 , 16 , 18 , 24 ]. Clinical symptoms were described in 11 patients [ 13 , 16 , 21 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen case reports regarding fishtail deformity including 58 patients were analysed [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The study and patient characteristics are shown in Table 3.…”
Section: Fishtail Deformitymentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies support conservative treatment for Kilfoyle grade I and II fractures, while grade III requires open reduction and internal fixation [ 1 , 2 , 5 , 13 ]. We agree with these previous studies on this point, but we still aggressively favor open reduction concerning complications such as secondary displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, similar to the lateral condyle fracture of the humerus, MCFH also requires anatomical reduction because of compromise to the articular surface and epiphysis. Delayed treatment can result in serious consequences such as osteonecrosis and cubitus varus [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%